EFEKTIVITAS MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH MENENGAH ATAS - Agryani Rosmaida Sitompul; Tiur Malasari Siregar (Universitas Islam Sultan Agung, 2026)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model in improving senior high school students’ critical thinking skills on the topic of function transformations. This research employed a quasi-experimental design with one experimental class taught using the PBL model. The subjects of the study were 30 students. The research instrument was a critical thinking test covering the following indicators: analyzing and formulating problems, providing further explanations, developing strategies and tactics, and drawing conclusions. Data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, N-Gain, and Cohen’s d. The result of the study showed that: (1) the average pretest score of 46,45 increased to 85,07 in the posttest, with a classical mastery level of 75%; (2) the t-test revealed a significant difference (Sig.0,05); (3) the mean N-Gain score was 0,73, categorized as high; and (4) Cohen’s d was 4,63 categorized as a very strong effect.Keywords: Problem-Based Learning, critical thinking skills, N-Gain, Cohen’s d, t-test